Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan Car Wash WS Sampit - Arbiansyah, Ihza (Universitas Darwan Ali, 2022)
The purpose of this research is to find out how the quality of service provided by the company and the price set can affect the satisfaction of customers who visit the Car Wash WS Sampit car wash. This sample was made using the Incidental Sampling method which to find these respondents is to ask by chance respondents who are at the place of the object of research, the total number of respondents is 100 people with each criterion including gender, age, and type of work. The instrument of this research is a questionnaire that uses a Likert scale to obtain information about customer satisfaction. Respondents were asked to answer each question with an assessment of strongly disagree, disagree, agree, and strongly agree. Multiple regression analysis is a technique used for data analysis. The results of the tests that have been carried out show a significant value of 0.000 <0.05, the service quality variable has a positive and significant impact on customer satisfaction. Thus H1 is approved but Ho is not approved. With a significant value of 0.001 <0.05, the price variable has a positive and significant impact on consumer satisfaction. Thus Ha is approved while Ho is not approved.